The intellectual contours of corporate social responsibility literature: Co-citation analysis study. Issue 11 (16th March 2020) - Bhattacharyya, Som Sekhar; Verma, Surabhi
Abstract : Purpose: Corporate Social Responsibility (CSR) deliberated regarding business firms' actions for doing well to society and natural environment. Specifically, CSR has been about firms contributions towards stakeholder management. As world economy has prospered over the last couple of centuries, business firms have had also increased its footprints in social landscape. In such a scenario, the roles and responsibilities of business firms have expanded in society. Over the years, CSR as a domain of research and literature has developed into a very potent and rich field. Presently, CSR literature as a body of knowledge has become substantial. The authors in this literature review study attempts to conceptually map this complex field of CSR literature. Design/methodology/approach: The objective of this literature review study was to present a visual mapping of intellectual structure of CSR in five-dimensions and to identify the subfields of CSR research concluded by co-citation analysis. All the citation research documents which were listed in the Web of Knowledge (WoK) database between 1998 and 2019 were analysed. Multivariate analysis was undertaken for the literature review. The study conducted a sequence of statistical analyses comprising of factor analysis, multidimensional scaling and cluster analysis. Findings: This literature review research study summarised the contours and status of CSR research by categorizing the CSR literature into five classification factors, namely CSR Drivers CSR, Contextual Grounding of CSR, Historical Legacy of CSR, Strategic CSR and CSR Implementation. Further, based upon the analysis of literature review of extant research in CSR, both the contemporary and imminent CSR-related research themes were also deliberated upon. Research limitations/implications: The results were helpful for academic scholars of CSR to comprehend both the gamut and focus of CSR literature over the years (between the years 1998 and 2019). The sequence of analyses involved factor, multidimensional scaling and cluster analysis. CSR literature was categorized into five factors namely- CSR Drivers, Contextual Grounding of CSR, Historical Legacy of CSR, Strategic CSR and CSR Implementation. Originality/value: This study was one of the first set of studies to review the literature on CSR research articles by using citation, co-citation and social network analysis.